Analysis of Cr(VI) Bioremediation by Citrobacter freundii Using Synchrotron Soft X-ray Scanning Transmission X-ray Microscopy - Amith G. Anil; Sufal Swaraj; Sankaran Subramanian; Praveen C. Ramamurthy (Quantum Beam Science, 2021)
Scanning transmission X-ray microscopy (STXM) was utilized for analysing the bioremediation of Cr(VI) by Citrobacter freundii, a species of gram-negative bacteria. The biosorption and bioreduction processes were analysed by the chemical mapping of cells biosorbed at different concentrations of Cr(VI). STXM spectromicroscopy images were recorded at O K-edge and Cr L-edge. A thorough analysis of the X-ray absorption features corresponding to different oxidation states of Cr in the biosorbed cell indicated the coexistence of Cr(III) and Cr(VI) at higher concentrations. This signifies the presence of partially reduced Cr(VI) in addition to biosorbed Cr(VI). In addition, the Cr(III) signal is intense compared with Cr(VI) at different regions of the cell indicating excess of reduced Cr. Speciation of adsorbed Cr was analysed for the spectral features of biosorbed cell and comparison with Cr standards. Analysis of absorption onset, L3/L2 ratio and absorption fine structure concludes that adsorbed Cr is predominantly present as Cr(III) hydroxide or oxyhydroxide. The evolution of absorption features in the duration of biosorption process was also studied. These time lapse studies depict the gradual decrement in Cr(VI) signal as biosorption proceeds. A strong evidence of interaction of Cr with the cell material was also observed. The obtained results provide insights into the biosorption process and chemical speciation of Cr on the cells.